Pengaruh Lingkungan Kerja dan Komunikasi Interpersonal Terhadap Kepuasan Kerja Pegawai di Kantor Dinas Pendidikan dan Kebudayaan Provinsi Kalimantan Timur - Tri Kusumawati; Damingun; Sylvia Priskila Anggela (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to analyze the effect of work environment and interpersonal communication on employee job satisfaction at the Office of Education and Culture (DISDIKBUD) of East Kalimantan Province. The problems raised include whether the work environment and interpersonal communication have a significant effect on employee job satisfaction, both individually and simultaneously. The research method used is a quantitative approach with data collection through a survey involving 71 respondents of DISDIKBUD employees. The data analysis technique uses multiple linear regression statistical tests to determine the effect of the independent variable on the dependent variable. The results showed that work environment and interpersonal communication have a significant influence on employee job satisfaction. Statistical tests indicate that both variables, both individually and simultaneously have a significant impact on job satisfaction. The coefficient of determination and the correlation coefficient indicate that variations in job satisfaction can be explained by both variables and show a strong relationship between the independent and dependent variables.